KELIMPAHAN DAN KARAKTERISASI MORFOLOGI BAKTERI COLIFORM PADA KALORA - Mahulette, Ferymon; Muskita, Christo; Melay, Stevin (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2022)
Background: Kalora is one of the processed fish foods consumed by the people in Maluku. The studies on food safety aspects of this processed food have never been carried out. One of the microbial groups used as an indicator of food safety is Coliform bacteria. This research aims to analyze the number and characteristics of Coliform bacteria in kalora. Methods: This research using three types of fish, i.e. white snapper (Lutjanus sp), scad mackerel (Decapterus sp), and tuna (Thunnus sp) as raw materials of kalora. Analysis of the number of Coliform bacteria used the Most Probable Number (MPN) method by inoculating the sample in lactose broth media, while macroscopic morphological characterization was carried out by streaking a positive tube sample on Eosin methylene blue agar (EMBA) media. Results: The results showed that snapper kalora had the highest MPN value of 9.2 MPN/g, followed by tuna and scad mackerel kalora at 6.2 MPN/g and 3.6 MPN/g, respectively. The characteristics of Coliform bacteria in kalora were varied but dominated by Escherichia and Enterobacter. Conclusion: The third types of kalora has the number of Coliform bacteria below the maximum treshold so it is safe for consumption.